Memberdayakan Siswa SMA Menciptakan Usaha Mikro Berbasis Aplikasi Pesan-Instan dan Media Sosial - Angelica Salsyabila A,P; Hedrian Saputra; Muhamad Abyzar Ramadhan (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology, with internet penetration in Indonesia reaching 64%, has created significant opportunities for the growth of the creative economy, particularly among the digital native generation at the high school level. This Community Service (PKM) activity aims to empower students at SMA Puspita Bangsa Ciputat to create micro-businesses based on instant messaging applications and social media to foster an independent and innovative entrepreneurial mindset. The implementation method was participatory, educational, and applied, involving visual material delivery, interactive discussions on real-world case studies such as